Vize’de (Kırklareli) yerleşmenin gelişimi - (:unkn) unknown (My University, 2011)
Vize, Kırklareli ilinde bir ilçenin yönetim görevini üstlenen küçük bir şehirdir. Makalede önce Vize’nin konumuna, kuruluş yerine ve kuruluşuna kısaca temas edilmiştir. Daha sonra yerleşmenin gelişimi dönemlere ayrılmış ve Cumhuriyet dönemi nispeten ayrıntılı bir şekilde ele alınmıştır. Bu son dönemde, yerleşmenin yatay ve dikey gelişimi, yapı malzemesi ve konut tipleri gibi özelliklere ağırlık verilmiştir.

Vize is a small city that has assumed the administrative function of a town in the Kırklareli province of Turkey. The paper first gives brief information about the location, place of establishment and establishment of Vize. Then, the development of the settlement is divided into specific periods, and the Republican period is dealt with in more details. The paper focuses on characteristics such as horizontal and vertical development and the types of construction materials and houses in this last period.
(Development of settlement in Vize-Kırklareli)
Keywords: Sanat